A comparison of address geocoding techniques – case study of the city of Zagreb, Croatia. Issue 359 (4th March 2018) - Cetl, V.; Kliment, T.; Jogun, T.
Abstract : In the last years a lot of online geocoding services have become available online. Some of them are based on VGI as input data. Such services are very useful in the case of big amounts of objects that need to be geocoded. However, the quality of such services has still not been adequately explored. In this paper we tried to answer several questions regarding the quality of online geocoding services using the city of Zagreb in Croatia as a research area. The results of research showed that the currently available services need improvements to provide accurate sources for geocoding.